The complete CPA reference - Dauber, Nicky A.; Shim, Jae K.; Siegel, Joel G.; Siegel, Joel G. (Hoboken, N.J. : Wiley, 2012)
The newly updated fast-reference problem solver The Complete CPA Desk Reference-the convenient, comprehensive reference professionals have relied on for nearly fifteen years-is now updated in a new Fifth Edition to give today's busy executives and accountants the helpful information they need in a quick-reference format. Packed with practical techniques and rules of thumb for solving day-to-day accounting issues, the new edition helps you quickly pinpoint what to look for, what to watch out for, what to do, and how to do it. In an easy-to-use Q & A format, it covers such useful.
Change in Accounting PrincipleChange in Accounting Estimate; Change in Reporting Entity; Correction of an Error; Prior-Period Adjustments; Disclosure of Accounting Policies; Development-Stage Companies; Troubled Debt Restructuring; Debtor; Creditor; Segmental Reporting; Imputing Interest on Notes; Accounting for Futures Contracts; Oil- and Gas-Producing Companies; CHAPTER 5 Key Financial Accounting Areas; Consolidations; Noncontrolling Interests in Consolidated Financial Statements; Business Combinations; Investments in Securities; Stock Investments; Market Value Adjusted; Equity Method.
Previous ed. published as The vest pocket CPA / Joel G. Siegel, Nick Dauber, Jae K. Shim. 2008.
Title from title screen.
Includes bibliographical references and index.
Keywords: Accounting -- Handbooks, manuals, etc; Accounting; Accounting -- Handbooks, manuals, etc; Financial statements; BUSINESS & ECONOMICS -- Accounting -- Financial; Accounting; Electronic books; Handbooks and manuals